Analysis of local surface displacement using repeated GPS measurements: a case study of the Guabirotuba area, Curitiba, Brazil - Amagua, Christian Gonzalo Pilapanta; Euriques, Jorge Felipe; Alves, Sergio da Conceição; Krueger, Claudia Pereira (Boletim de Ciências Geodésicas, 2022)
In recent years, the ability of GNSS systems to estimate high accuracy 3D positions has greatly contributed to the development of new monitoring techniques aimed at understanding the mechanisms by which the different Earth processes are generated. This paper presents the result of 9 GPS campaigns, between 2014 and 2019 for a group of 29 stations, held in the Guabirotuba urban area, Curitiba, Brazil, intending to estimate local crustal movements. The average magnitude and direction of horizontal velocities obtained for each site, allow demonstrating deformation of the southern zone of the area as a result of a local landslide process. The magnitude of the vectors varies between 1 and 16 mm/a horizontally. All sites had an absolute vertical movement, probably correlated with a local geological pattern or a physical site’s motion driven by environmental mass redistribution. The uncertainties in positions and velocities for a long-term survey (over 5 years), showed good consistency at most sites when compared with the coordinates and velocities precision of the latest SIRGAS solution. The typical precision for the station positions at the reference epoch was ±2 mm horizontally and ±5 mm vertically, and ±0.60 mm/a horizontally and ±1.37 mm/a vertically for the constant velocities.